Herbicide selectivity and weed control in gladiolus cultivation - Wesz, Alessandra Minuzzi; Polidorio, Laura; Barbieri, Geovana Facco; Uhlmann, Lilian Osmari; Tomiozzo, Regina; Guarienti, Veronica Fuzer; Streck, Nereu Augusto; Ulguim, André da Rosa (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the selectivity of pre- and post-emergent herbicides and their efficiency in weed control, as well as the growth and quality of floral stems, in a gladiolus (Gladiolus x grandiflorus) crop in two growing seasons. The experiments were carried out in the field, where the planted gladiolus received the application of pre- and post-emergent herbicides, with and without mechanical weed control. At 7, 14, 21, and 28 days after emergence (DAE), monocotyledon and eudicotyledon control and phytotoxicity to gladiolus plants were evaluated. At 28 DAE, the shoot dry matter of weeds and gladiolus plants was also evaluated. The s-metolachlor and diuron pre-emergent herbicides and the haloxyfop-p-methyl post-emergent herbicide are selective to gladiolus plants in both seasons, which allows of the production of floral stems with commercial quality. The s-metolachlor and haloxyfop-p-methyl herbicides also promote an efficient control of monocotyledons regardless of the growing season. Although, when applied, saflufenacil and 2,4-D cause phytotoxicity in the vegetative phase of gladiolus, they do not affect the production of floral stems and control satisfactorily eudicotyledons in the second season.
Keywords: Gladiolus x grandiflorus; floriculture; phytotoxicity; post-emergence; pre-emergence; quality standard